10.162 The Global Research Progress of Enzymatic Processing of Oils with Omega 3 Polyunsaturated Fatty Acids - Dilay Sen; Derya Kahveci (Liang you shipin ke-ji, 2020)
This paper has reviewed that Omega 3 polyunsaturated fatty acids (PUFAs)，as an essential fatty acids (EFAs)，mainly come from fish oil of marine products，has positive effects on treatment and/or prevention of several diseases.In this review，the recent developments by 2019 in the field of enzymatic modification of oils rich in omega 3 PUFAs have summarized.Several different products，such as structured lipids with a variety of FA compositions，nutritional aspects，omega 3 PUFA concentrates and phospholipids，have discussed from the point of process technology as well as possible applications.Enhancing omega 3 PUFA content in diet involves a number of strategies aiming to modify the content of such FAs in fats and oils.Due to the mild reaction conditions used，especially the lipase specificity，the position as well as content of omega 3 PUFAs in lipid molecules being of importance from the point of bioavailability，enzymatic processing of omega 3 PUFA oil is safe，efficient and preferred over chemical treatments.